2001
DOI: 10.1121/1.1370525
|View full text |Cite
|
Sign up to set email alerts
|

The acoustic bases for gender identification from children’s voices

Abstract: The purpose of this study was to examine the acoustic characteristics of children's speech and voices that account for listeners' ability to identify gender. In Experiment I, vocal recordings and gross physical measurements of 4-, 8-, 12-, and 16-year olds were taken (10 girls and 10 boys per age group). The speech sample consisted of seven nondiphthongal vowels of American English (/ae/ "had," /E/ "head," /i/ "heed," /I/ "hid," /a/ "hod," /inverted v/ "hud," and /u/ "who'd") produced in the carrier phrase, "S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
127
1
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(149 citation statements)
references
References 30 publications
15
127
1
6
Order By: Relevance
“…Indeed, young language learners begin to show preferential patterns of language acquisition early on in production. For example, children show gender-specific speech patterns prior to the onset of puberty-induced anatomical differences (Sachs et al 1973;Perry et al 2001; though see Vorperian et al [2009] for recent evidence of sex differences in vocal tract anatomy prior to puberty). This suggests that gendered speech patterns are at least somewhat learned, with young boys and girls modeling their speech patterns on select input, not an aggregate of all spoken language they have been exposed to.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, young language learners begin to show preferential patterns of language acquisition early on in production. For example, children show gender-specific speech patterns prior to the onset of puberty-induced anatomical differences (Sachs et al 1973;Perry et al 2001; though see Vorperian et al [2009] for recent evidence of sex differences in vocal tract anatomy prior to puberty). This suggests that gendered speech patterns are at least somewhat learned, with young boys and girls modeling their speech patterns on select input, not an aggregate of all spoken language they have been exposed to.…”
Section: Introductionmentioning
confidence: 99%
“…These findings imply that, overall, boys have larger vocal tracts than girls. In [6], statistical analysis of children speech confirmed that formant frequencies (F1, F2, F3), and not F0, differentiate gender for children as young as four years of age, while formant frequencies plus F 0 differentiate gender after 12 years of age. These findings lead to the conclusion that for preadolescent children, vocal tract measures play a bigger role for gender classification than the voice source measure F 0 .…”
Section: Introductionmentioning
confidence: 85%
“…Ao avaliar a f 0 e frequências dos três primeiros formantes, um grupo de autores 27 apontou diferenças somente a partir dos 11 anos de idade. Outros pesquisadores 28 concluíram que embora a análise das frequências dos formantes tivesse permitido a diferenciação entre os sexos em crianças a partir de quatro anos de idade, a análise da f 0 só pôde diferenciar os sexos a partir dos 12 anos.…”
Section: Sexosunclassified